Jack C. Richards' 50 tips for teacher development - Richards, Jack C. 1943- (Cambridge handbooks for language teachers, 2017)
This book offers 50 practical ideas for teachers to use for professional development. The tips cover a wide range of activities that can be carried out individually or in collaboration with others, including self and peer observation, journal writing, on-line forums, classroom research, action research, team teaching, lesson review, materials review, lesson study, mentoring, peer coaching, reading groups, and workshops. Each tip is described in a 2 two-page format that gives the rational for the activity and step-by-step procedures for implementing it. The Tips can be used with both novice and more experienced teachers and are intended to provide a basis for teachers to review the current state of their professional learning and to develop and implement goals for their professional development